The distal dorsalis pedis flap for nasal tip reconstruction - (:unkn) unknown (CHURCHILL LIVINGSTONE, 1996)
Local flaps offer the most suitable tissues for nasal tip reconstruction and with multistaged operative procedures excellent cosmetic results can be achieved in recreating the deficient nasal features. When local flaps or multistaged procedures cannot be performed, nasal tip reconstruction becomes a great challenge for the surgeon. A case is reported in which the dorsal skin of the second toe and the first two web spaces was transferred as a free flap over a framework of conchal and septal cartilage grafts to reconstruct a nasal tip.